Boosting molecular oxygen activation ability in self-assembled plasmonic p-n semiconductor photocatalytic heterojunction of WO3/Ag@Ag2O - Liang, Chao; Guo, Hai; Zhang, Lei; Ruan, Min; Niu, Cheng-Gang; Feng, Hao-Peng; Wen, Xiao-Ju; Tang, Ning; Liu, Hui-Yun; Zeng, Guang-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
•The prepared hybrid composite possesses enhanced molecular oxygen activation.•The plasmonic p-n heterojunction exhibits high hot charge carrier separation.•The detailed degradation intermediate transfer pathway is proposed.•The band gap position alignment is thoroughly investigated. In recent years, many efforts have been devoted to boost molecular oxygen activation in semiconductor. This is because the reactive oxygen species (ROS) induced by molecular oxygen activation have been confirmed to play a great role in environmental remediation. Herein, we proposed a self-assembled plasmonic p-n heterojunction of WO3/Ag@Ag2O with enhanced molecular oxygen activation ability under visible and near-infrared (NIR) light irradiation. The prepared p-n heterojunction is favorable for the migration and separation of photo-generated hot charge carriers, which can promote the transformation of molecular oxygen to ROS with enhanced photocatalytic performance for norfloxacin (NOR) decomposition. The trapping experiments and Electron spin response (ESR) spectra demonstrate that both superoxide (O2−) and singlet oxygen (1O2) are the main functional ROS for NOR degradation. The yield amount of O2− in the prepared hybrid catalyst is higher than that of pristine catalyst from nitrotetrazolium blue chloride (NBT) degradation. The sustainable generation of 1O2 is mainly ascribed to the charge transfer and energy transfer. Fluorescence spectra method is employed to confirm the generation of hydrogen peroxide (H2O2). The intermediates of NOR degradation are identified by LC/MS, and the possible degradation pathway is proposed in detail. A reasonable charge transfer pathway for the ultra-high hot charge carrier separation is studied. In addition, the as-prepared hybrid composite shows excellent photocatalytic performance for the degradation of rhodamine B (RhB) and ciprofloxacin (CIP). This study provides a promising avenue for fabrication of semiconductor with boosting molecular oxygen activation.